FUNGSI SHUUJOSHI DIALEK KANSAI DALAM FILM SETOUTSUMI - I Putu Wipayana; Ni Wayan Meidariani; Ni Luh Gede Meilantari (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2021)
This research aims to determine and describe the types and functions of shuujoshi Kansai dialect contained in the Setoutsumi movie. This research is descriptive - qualitative. The data source used in this research is the dialogue in the Setoutsumi movie. Data were analyzed using theory of shuujoshi Kansai dialect proposed by Makiko, et al. This research used the Simak method with the advanced technique of noting as a method and data collection technique, by watching to the Setoutsumi movie, then taking note the dialogue that using shuujoshi Kansai dialect. Methods and data analysis techniques that using is descriptive qualitative methods. Then, it is presented using an informal method, which is presented in Indonesian language with more easier to understand. The results show that in the Setoutsumi movie there are three types of shuujoshi Kansai dialect, that is shuujoshi na which function to ask for approval. Shuujoshi ya function to make strong requests. As well as shuujoshi de serves to provide information.